2021
DOI: 10.3354/meps13561
|View full text |Cite
|
Sign up to set email alerts
|

Short-term responses to ocean acidification: effects on relative abundance of eukaryotic plankton from the tropical Timor Sea

Abstract: Anthropogenic carbon dioxide (CO2) emissions drive climate change and pose one of the major challenges of our century. The effects of increased CO2 in the form of ocean acidification (OA) on the communities of marine planktonic eukaryotes in tropical regions such as the Timor Sea are barely understood. Here, we show the effects of high CO2 (mean ± SD pCO2 = 1823 ± 161 μatm and pHT = 7.46 ± 0.05) versus in situ CO2 (504 ± 42 µatm, 7.95 ± 0.04) seawater on the community composition of marine planktonic eukaryote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…An early study by Tortell and Morel [ 64 ] demonstrated that HCO 3 − uptake in the equatorial Pacific Ocean is regulated by the ambient CO 2 concentrations, where phytoplankton assemblages did not express eCA under high CO 2 concentrations (750 µatm). Several studies observed a reduction in eCA activity as a response to high CO 2 concentrations (800 µatm) in diatom assemblages of the West Antarctic Peninsula [ 65 , 66 , 67 ] and more recently in the Timor Sea phytoplankton assemblages [ 18 , 68 ]. Contrarily, tolerance of highly variable CO 2 levels has been observed for diatom assemblages in the subarctic Pacific, indicating that the direct uptake of HCO 3 − dominates carbon uptake for these assemblages [ 69 ].…”
Section: Extracellular Carbonic Anhydrase In a Changing Oceanmentioning
confidence: 99%
“…An early study by Tortell and Morel [ 64 ] demonstrated that HCO 3 − uptake in the equatorial Pacific Ocean is regulated by the ambient CO 2 concentrations, where phytoplankton assemblages did not express eCA under high CO 2 concentrations (750 µatm). Several studies observed a reduction in eCA activity as a response to high CO 2 concentrations (800 µatm) in diatom assemblages of the West Antarctic Peninsula [ 65 , 66 , 67 ] and more recently in the Timor Sea phytoplankton assemblages [ 18 , 68 ]. Contrarily, tolerance of highly variable CO 2 levels has been observed for diatom assemblages in the subarctic Pacific, indicating that the direct uptake of HCO 3 − dominates carbon uptake for these assemblages [ 69 ].…”
Section: Extracellular Carbonic Anhydrase In a Changing Oceanmentioning
confidence: 99%
“…We chose abundance as our response variable because abundance or its co-variate, biomass, is the most commonly measured variable in long-term monitoring studies, including those that have been used to detect changes due to ocean condition (e.g., Hays et al, 2005;Mackas and Beaugrand, 2010;McKinstry and Campbell, 2018). Moreover, abundance has been used to detect response to change in short-term studies of marine microbes (Currie et al, 2017;Rahlff et al, 2021).…”
Section: Matching Experimental Data With Field Observationsmentioning
confidence: 99%